Susceptibility of Rhipicephalus rutilus ticks from dogs to different acaricides - Marcos Antonio Bezerra-Santos; Filipe Dantas-Torres; Nicola Pugliese; Mara Miglianti; Wafa Rhimi; Claudia Cafarchia; Domenico Otranto (Ticks and Tick-Borne Diseases)
Brown dog ticks (Rhipicephalus sanguineus sensu lato) are widespread ectoparasites of dogs and may also infest other vertebrate hosts, including humans. The control of these ticks is primarily carried out using acaricides. In this study, we assessed the susceptibility of Rhipicephalus rutilus to different acaricides (i.e., amitraz, fipronil, ivermectin, and permethrin). Engorged female ticks (n = 36) were divided into three groups based on their origin (i.e., G1 – untreated dogs from a private shelter; G2 – permethrin-treated private dog shelter; and G3 - fipronil, amitraz, and (S)-methoprene treated owned dogs) and kept under controlled temperature and humidity for oviposition. The acaricidal effects of amitraz (AMZ), fipronil (FIP), ivermectin (IVM), and permethrin (PTR) against R. rutilus were evaluated using the larval packet test, with subgroups of tick larvae in each experimental assay. Our data indicate that R. rutilus larvae from all dog groups were susceptible to IVM. In particular, larvae from G1 were apparently susceptible to IVM and PTR, and tolerant to AMZ and FIP; larvae from G2 were susceptible to FIP and IVM and resistant to AMZ and PTR, while larvae from G3 were susceptible to AMZ, PTR and IVM, and resistant to FIP. These results confirm the occurrence of resistance to AMZ, PTR, and FIP in R. rutilus larvae from southern Italy. This suggests the need to monitor acaricide resistance in brown dog ticks in southern Europe to develop better strategies for the long-term control of ticks in this region.